A case of Hirschsprung’s disease with segmental dilatation of the colon - Hideyuki Yokokawa; Mariko Yoshida; Shinya Takazawa; Mai Kutsukake; Kanako Omata; Shoko Ogawa; Jun Fujishiro (Surgical Case Reports)
Abstract Background Segmental dilatation of the colon (SDC) is a rare disease that is characterized by an abrupt segment of dilated colon between regions of normal-sized colon. We herein report a case of SDC associated with Hirschsprung’s disease (HD). Case presentation The patient developed abdominal distension soon after birth, and enema examination showed localized intestinal dilatation from the descending colon to the sigmoid colon with significant caliber changes on both the oral and anal sides of the dilated colon. The findings of the rectal mucosal biopsy were consistent with HD. We considered this case to be a combination of HD and SDC and performed laparoscopic-assisted Soave pull-through with resection of the dilated colon when the patient was 7 months old. Resected specimens showed steep caliber changes on the oral and anal sides of the dilated colon. In the pathological examination, no ganglion cells were found in the submucosa on the anal side of the dilated colon. Based on the above findings, we finally made the diagnosis of HD with SDC. Conclusion In HD with a characteristic dilated colon, the possibility of SDC should be considered.